A symmetry roadmap to new perovskite multiferroics. Issue 4 (6th July 2018) - Woodward, Patrick M.
Abstract : The new approach to the design of technologically important perovskites described by Senn and Bristowe [ Acta Cryst. (2018), A74, 308–321 ] is discussed. Abstract : The new approach to the design of technologically important perovskites described by Senn and Bristowe [ Acta Cryst. (2018), A74, 308–321 ] is discussed.